A method of reducing the radial load of the shaft of a vertical axis wind turbine based on movable mass blocks. (September 2021) - Zhang, Lijun; Miao, Junjie; Gu, Jiawei; Li, Xiang; Hu, Kuoliang; Zhu, Huaibao; Sun, Xuefa; Liu, Jing; Liu, Yanxin; Wang, Zhiwei
Abstract: Fatigue failure caused by unsteady loads on the shaft is an important limiting factor in the development of large VAWT. This study proposes an active control method that relies on movable mass blocks to reduce the unsteady loads. Then on the basis of the aerodynamic load of the VAWT simulated by computational fluid dynamics, the motion laws of the mass blocks with different masses are investigated. When the mass of mass block is 0.075 kg, the radial load of the shaft can be reduced by 97.1% and the shaft deformation can be eliminated by 99% without affecting the power output of wind turbine. However, further research on the start-up performance of the VAWT indicates that the active control method also prolongs the start-up time. Thus a method of adjusting the moment of inertia of wind turbine with a rotation speed of 15.6 m/s is proposed to save 40.6% of the start-up time with respect to the method used for direct start-up with large moment of inertia of 0.036 kg m 2 . After the start-up, a transition displacement curve is plotted to aid in the switching design of the operation mode of mass blocks between the start-up phase and the normal operation phase.